Cidades acolhedoras para a primeira infância: caminhos para o desenvolvimento sustentável – a experiência do município de São Paulo - Pessoni, Isabela Grilo (2023)
Early childhood is a crucial phase for human development and cities play a key role in creating nurturing environments that promote healthy growth. The study seeks to understand how the integrated early childhood policy established in the capital contributes to the construction of more welcoming and sustainable cities. For that, a bibliographic survey was used, having as a parameter guidelines for public managers in urban planning, considering the needs of early childhood: I) decision-making based on data, II) public spaces and nature, III) mobility for families and IV) use of services. An analysis was carried out to identify how these parameters were incorporated into the Integrated Early Childhood Policy in the city of São Paulo. Through an exploratory analysis based on documents and reports on monitoring and evaluation of the public administration with this theme, it was possible to identify the main measures adopted by the municipality and how they cover the strengthening of a governance system and expansion of the offer of services. There are challenges in ensuring the intersectoriality of policies and in establishing the monitoring and evaluation of actions in an integrated manner. It was demonstrated how the goals and forecasts of the municipal policy are aligned with the global sustainable development agenda, its advances and limitations between the years 2019 and 2021.